Stable Bismuth‐Doped Lead Halide Perovskite Core‐Shell Nanocrystals by Surface Segregation Effect. Issue 3 (27th November 2021) - Zhu, Jingrun; Zhou, Lihui; Zhu, Yihua; Huang, Jianfei; Hou, Lu; Shen, Jianhua; Dai, Sheng; Li, Chunzhong
Abstract: Lead halide perovskite nanocrystals (NCs) exhibit excellent optoelectronic performance, however, the broad application is limited by their poor stability. Herein, a strategy for stable core‐shell structured bismuth‐doped lead halide perovskite NCs is reported. The stable core‐shell perovskite NCs are prepared based on heterovalent substitutions and surface segregation effect. Core‐shell features are revealed through advanced characterization and structure analyses. Meanwhile, the transfer of carriers between the core and the shell is observed by ultrafast transient absorption spectroscopy. The core‐shell structured perovskite NCs exhibit outstanding structure stability and retain 97% of the original photocatalytic efficiency after cycle experiments under moisture ambient and light irradiation. Such a core‐shell structure constructs gradient energy levels. These findings are expected to facilitate the development of stable lead halide perovskite devices. Abstract : A strategy for stable Bi‐doped lead halide perovskite nanocrystals (NCs) with core‐shell structure by the surface segregation effect originating from heterovalent doping, which overcomes the obstacles caused by hydrophobic surface of perovskite NCs, is pursued. The Bi‐rich shell endows Bi‐doped CsPbCl3 NCs superior stability against the strong irradiation, high humidity, CO2, and O2 ambient.